Thermodynamics of cumulus clouds - De Roode, Stephan R. (Física de la Tierra, 2008)
Mixing diagrams are investigated to explore whether mixing of undiluted (adiabatic) cumulus cloud air with clear air from its environment can lead to buoyancy reversal, i.e. mixed parcels that are saturated and negatively buoyant with respect to the dry environment. It is demonstrated that buoyancy reversal will always occur at any mixing height. It is also shown that the virtual potential temperature difference between a mixed parcel and the environment is most negative at the top of the cloud. The role of the mean state structure on the buoyancy of mixed parcels is discussed. The analytic expression describing the form of the mixing diagram is shown to be identical to the cloud-top entrainment instability criterion originally derived for a stratocumulus cloud layer capped by an inversion.